2015
DOI: 10.1590/01000683rbcs20140289
|View full text |Cite
|
Sign up to set email alerts
|

Seleção De Densidade De Amostragem Com Base Em Dados De Áreas Já Mapeadas Para Treinamento De Modelos De Árvore De Decisão No Mapeamento Digital De Solos

Abstract: reSUmo para estudar técnicas de amostragem, úteis ao mapeamento digital de solos (mdS), objetivou-se avaliar o efeito da variação da densidade de pontos amostrais com base em dados de áreas já mapeadas por métodos tradicionais na acurácia dos modelos de árvores de decisão (AD) para a geração de mapas de solos por MDS. Em duas bacias hidrográficas no noroeste do rio grande do Sul, usou-se, como referência, antigos mapas convencionais de solos na escala 1:50.000. A partir do modelo digital de elevação do terreno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
2
6
0
1
Order By: Relevance
“…However, Giasson et al (2013) observed an average K of 0.37 in the Lajeado Grande watershed, which shows characteristics similar to the area of the present study. Likewise, Bagatini et al (2015) obtained a GA similar to those in the present study; in their study, depending on the sampling point density, GA varied between 60 and 76% in the Rio Santo Cristo watershed, and between 54% (lowest density, 0.1 points ha -1…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…However, Giasson et al (2013) observed an average K of 0.37 in the Lajeado Grande watershed, which shows characteristics similar to the area of the present study. Likewise, Bagatini et al (2015) obtained a GA similar to those in the present study; in their study, depending on the sampling point density, GA varied between 60 and 76% in the Rio Santo Cristo watershed, and between 54% (lowest density, 0.1 points ha -1…”
Section: Resultssupporting
confidence: 88%
“…This GA behavior was similar to that observed in the Carajazinho chart, which belongs to the same physiographic region evaluated by Giasson et al (2013) and Bagatini et al (2015).…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…De modo geral, a reprodutibilidade do mapa convencional de solos (Tabela 4) com os dados coletados apenas nos pixels dos perfis de solos alcançou valores próximos ao valor médio de 60% observado na literatura em estudos com outras estratégias de amostragem utilizada no mapeamento digital de solos (Höfig et al, 2014;Giasson et al, 2015;Bagatini et al, 2016;Dias et al, 2016;Pelegrino et al, 2016). Vale destacar que em ambas as áreas de estudo apenas duas unidades representam mais de 75% da composição dos respectivos mapas de solos, sendo estas as mais importantes na predição e as quais apresentaram maior concordância com os mapas legados utilizados na validação.…”
Section: /9unclassified
“…This approach allowed better distribution of points across polygons, as opposed to random sampling, which tends to provide greater density of points in large polygons, thus reducing the importance of the information contained in small polygons (Odgers et al, 2014). The point density chosen was approximately 2.5 points per hectare, as suggested by Sarmento et al (2012) and Bagatini et al (2015) for sampling density in DSM. The sampling process resulted in selection of approximately 50,000 sampling points in the WDS area and approximately 38,000 sampling points in the IPDS area for use in the predictive model.…”
Section: Assignment Of Soil-landscape Relationships and Creation Of Tmentioning
confidence: 99%